An evaluation of the intercultural communication competence of Filipino engineering students in communicating with other Southeast Asians - Lagman, Kyla Hope Ablan 1999-; Natividad, Francis Elliot B.; Paragas, Fernando dlC; University of the Philippines Diliman. College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2019)
As ASEAN integration is concerned with mobility within industries involving engineers, the current evaluates the intercultural communication competence (ICC) of Filipino engineering students in communication with other Southeast Asians. It utilizes both quantitative methods to analyze the effective, cognitive, and behavioral dimensions of ICC in light of educational environments and individual manifestations of ethnocentrism. The inquiry was guided by an integration of Chen & Starosta's (1996) Dimensions of Intercultural Communication, Bandura's (1986) Social Cognitive Theory, and BEnnet's (1986) Developmental Model for Intercultural Sensitivity. A total of 400 survey respondents and 17 informants,. all Filipino engineering students in Metro Manila, were sampled from randomly selected ABET-accredited degree programs and their non-ABET-accredited counterparts. Data from both sources produces a holistic view of the current state of ICC among Filipino engineering students in Metro Manila. Filipino engineering students perceive themselves to be well-equipped with ICC in interactions with other Southeast Asians. However, their ICC is only weakly determined by their experiences of intercultural communications as part of their environment. Furthermore, Filipino culture remains central to their views of cultural difference and definitions of competent behavior in relation to other Southeast Asians.
Vita.
Thesis (A. B. Communication Research)--University of the Philippines Diliman
Includes bibliographical references.
Keywords: Communicative competence; Intercultural communication in education